Establishing a design for passive vertical flow constructed wetlands treating small sewage discharges to meet British Standard EN 12566. Issue 2 (17th January 2017) - Weedon, Christopher Michael; Murphy, Clodagh; Sweaney, Geoff
ABSTRACT: Owing to legislation change (which made General Binding Rules effective from 1 January 2015) unless discharge is to specified environmentally sensitive sites, small sewage discharges (SSDs) in England – that is, <2 m 3  d −1 to ground; <5 m 3  d −1 to surface waters – no longer require an Environmental Permit (EP) and need not be registered for exemption, provided discharge to surface waters is preceded by treatment using equipment complying with BS EN 12566. This effectively excludes the use of treatment wetlands, unless covered by an EP, because the cost of certification to EN 12566 for bespoke designs is prohibitive. EPs take up to four months to obtain. Therefore, the new legislation has created a commercial disadvantage for constructed wetlands treating SSDs, compared with mass-produced sewage treatment plants. However, the UK statutory pollution regulators have maintained a dialogue with the Constructed Wetland Association (CWA), with a view to assessing whether treatment of SSD using constructed wetlands might be allowable, without requiring EPs. This paper presents treatment performance data obtained over 15 years, from a variety of full-scale operational treatment wetlands, as supporting evidence for design guidelines, proposed by the CWA to the UK regulators, for the implementation of constructed wetlands continuously passively treating SSD to 20:30:20 mg l −1 BOD/SS/NH4-N under a wide range of loading rates. Relevant experience of UK designers, installers and operators since the early 1990s is included, resulting in recommended physical design criteria and loading rates for compact vertical flow reed beds, presented here as key elements of the draft guidelines.